Pengaruh Metode Resitasi dan Motivasi Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam - Tujuh, Syarifah HR DG; Fitriyanti, Fitriyanti (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The study aims to test how much influence the recitation and motivation methods have on the learning outcomes of the students in Islamic education subjects at the 1st Bakam State High School. The research method used is a quantitative method, using double linear regression as a data analysis technique. The results of the instrument validation showed a reliability coefficient of 0.770 for the instrument of the recitation method, whereas for the motivation instrument, the reliability factor was 0.722. The results of the data analysis showed that there was a positive and significant influence between the method of recitation and motivation on the learning outcomes of the students in Islamic education subjects at State High School 1 Bakam. Data analysis results with the equation of regression Y=5.959+0.875X1+1.165X2. This equation shows that when the method increases by one unit, the learning results increase by 0.875.